1969
DOI: 10.1128/jb.98.3.1069-1072.1969
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Composition of Deoxyribonucleic Acid of Some Species ofCryptococcus, Rhodotorula, andSporobolomyces

Abstract: The buoyant density of deoxyribonucleic acid (DNA) from nine species and two varieties of Cryptococcus, three species and two varieties of Rhodotorula, and six species of Sporobolomyces was determined by CsCl density gradient equilibrium centrifugation. Several species were represented by two to four different strains. Expressed in moles per cent of guanine plus cytosine (GC content) the ranges were 49 to 65%, 52 to 70%, and 51 to 65% for Cryptococcus, Rhodotorula, and Sporobolomyces, respectively. For each ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Values in the higher range have been reported for Candida (38,44), some species of Torulopsis and Trichosporon, and for all species studied of Cryptococcus, Rhodotorula, and Sporobolomyces (38). More recently (46), an analysis of additional species and varieties of Cryptococcus, Rhodotorula, and Sporobolomyces has shown that with one exception, a Cryptococcus species, the %GC was in all cases higher than 50 and averaged 58.1. All these investigations reinforce the contention formulated earlier (45) that yeast and yeastlike fungi which are related to the Heterobasidiomycetes have a GC content which is significantly higher than that of those organisms classified as Hemiascomycetidae or their anascosporogenous counterparts.…”
Section: Introductionmentioning
confidence: 80%
“…Values in the higher range have been reported for Candida (38,44), some species of Torulopsis and Trichosporon, and for all species studied of Cryptococcus, Rhodotorula, and Sporobolomyces (38). More recently (46), an analysis of additional species and varieties of Cryptococcus, Rhodotorula, and Sporobolomyces has shown that with one exception, a Cryptococcus species, the %GC was in all cases higher than 50 and averaged 58.1. All these investigations reinforce the contention formulated earlier (45) that yeast and yeastlike fungi which are related to the Heterobasidiomycetes have a GC content which is significantly higher than that of those organisms classified as Hemiascomycetidae or their anascosporogenous counterparts.…”
Section: Introductionmentioning
confidence: 80%
“…Sequence analysis [11] demonstrated that S. marcillae and S. pararoseus were phylogenetically distinct. This taxonomic distinction was indicated by di¡erences in DNA base composition: 55.0 mol% for S. marcillae strain CBS 4217, and 51.5 mol% for S. pararoseus strain CBS 484 [15]. Strains of S. roseus were isolated from plants, soils and human diseases [16].…”
Section: Resultsmentioning
confidence: 99%
“…The average GC content for a single strain of C. albidus tested at that time was also higher than the average range for most ascomycetes, but would easily fall into the GC content range for basidiomycetes. More recently, Storck and his colleagues (14) reported on their determination of GC content of DNA extracted from a number of individual species of Cryptococcus, Rhodotorula, and Sporobolomyces. Their findings, which confirm and extend the earlier report by Storck (13), suggest that determination of the GC content of DNA may be essential for any future definitive taxonomic or phylogenetic studies of the yeasts and yeastlike fungi.…”
Section: Discussionmentioning
confidence: 99%